2012
DOI: 10.2215/cjn.06840711
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Levels, Endothelial Dysfunction, and the Risk of Cardiovascular Events and Mortality in Patients with CKD

Abstract: SummaryBackground and objectives Both prolactin clearance and production are altered in CKD. In nonrenal populations, emerging evidence suggests that prolactin participates in the atherosclerotic process. Given the elevated cardiovascular risk of CKD, this study examined links between prolactinemia, vascular derangements, and outcomes.Design, setting, participants, & measurements This observational study was conducted in two cohorts: one with 457 nondialyzed CKD patients (mean age 52612 years; 229 men) with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 42 publications
7
82
0
7
Order By: Relevance
“…Few studies have investigated the potential role of prolactin in the increased risk of cardiovascular events, e.g. essential hypertension, the heart failure that accompanies Peripartum cardiomyopathy, and arrhythmias (7,22). On the other hand, the positive influence of prolactin on the cardiovascular system was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the potential role of prolactin in the increased risk of cardiovascular events, e.g. essential hypertension, the heart failure that accompanies Peripartum cardiomyopathy, and arrhythmias (7,22). On the other hand, the positive influence of prolactin on the cardiovascular system was shown.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone may also affect the vascular bed by regulating structural elements of the arterial wall, including collagen, elastin and fibrillin-1 56) . In the Baltimore Longitudinal Study of Aging, a low serum testosterone level was found to be a risk factor for AS, suggesting a cause and effect relation-in the CKD 5D patients 37) . The authors suggested that prolactin retention in CKD patients may be a contributing factor to vascular derangement and worse cardiovascular outcomes.…”
Section: Testosteronementioning
confidence: 98%
“…The major risk factors for an increased level of prolactin are reduced renal clearance and increased production of the hormone 36) . Hyperprolactinemia is associated with infertility, gynecomastia, galactorrhea, loss of libido and mortality in CKD patients 37) .…”
Section: Prolactinmentioning
confidence: 99%
“…In patients with chronic kidney disease, PRL level is directly associated with endothelial dysfunction and within increased risk of cardiovascular events and mortality [12]. Furthermore, even with PRL levels in the normal range, a positive association has been found between higher PRL tertiles and all-cause and cardiovascular mortality in both sexes and cancer deaths in men [6].…”
mentioning
confidence: 99%
“…However, the PRL multiple metabolic effects, leading to metabolic syndrome, are well-documented in animal and human cell lines studies [2][3][4]. Furthermore, several clinical studies with a few patients-have shown us the metabolic benefit of hyperprolactinemia treatment [1,[7][8][9][10][11][12].…”
mentioning
confidence: 99%